BRIDGING THE DIVIDE: THE ORDEALS AND TRIUMPHS OF A BLACK MAN IN WHITE AMERICA - Alam Zeb; Mubashir Ahmad; Irfan Ullah Khan (PalArch's Journal of Archaeology of Egypt / Egyptology, 2023)
The study of any aspect of African-American society necessitates an examination of its history, as their unique experiences have profoundly influenced their lives. Literature serves as a verbal expression of a community's thoughts and emotions, making an understanding of the factors that shape their imagination and thinking patterns crucial for analyzing their literary works. According to Houstoun A. Baker Jr., Black Literature in America (1971), much like the Black American population, is largely a product of social circumstances. Studies in Afro-American literature often incorporate socio-historic perspectives. A comprehensive understanding of the black community's history is essential for examining any literary trend or aspect. This particular study aims to assess the influence of black nationalism and black Muslim movements on African-American literature. However, to fully grasp the significance, it is crucial to explore the socio-political and religious implications of the Islamic experience and the underlying conditions that contributed to this phenomenon.